(untitled) (InKoj. Philosophy & Artificial Languages, New series, 2010)
It is possible to classify Artificial Languages as well as Natural Languages into three main types, according to the forms of comparative adjectives. Artificial Languages can form the comparatives using only a synthetic strategy, or only an analytic strategy, or both of them accordingly. Artificial Languages that use only a syntetic strategy can be classified further according to the rules in choosing one strategy or the other. Some evidence shows that a large proportion of Artificial Languages have both analytic and synthetic comparatives, as in some natural languages. The formation of comparatives results to be an interesting area of morphology, where there is room for choice, also for Artificial Languages. Eblas klasifiki artefaritajn kaj naturajn lingvojn laŭ tri tipoj, depende al la formoj de komparativaj adjektivoj. Artefaritaj lingvoj povas formi komparativojn uzante nur sintezajn formojn, nur analizajn formojn, aŭ ambaŭ formojn laŭkaze. Artefaritajn lingvojn kiuj uzas nur sintezan strategion oni povas klasifiki plue per la reguloj elekti unu aŭ la alian strategion. Ia evidenco montras, ke granda parto de artefaritaj lingvoj havas ambaŭ analizan kaj sintezan komparativojn, kiel en kelkaj naturaj lingvoj. La formado de komparativoj rezultas esti interesa areo de morfologio, en kiu eblas elekti, eĉ kaze de artefaritaj lingvoj.